The Use Of Question And Answer Method To Improve Student Achievement - Ismiyatun Ismiyatun (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The aim of this research is to determine the increase in student learning achievement in science subjects regarding animals adapting to their environment through the media of images. This research is a type of Classroom Action Research which was carried out in 2 cycles. The subjects of this research were 22 class V students at Mlese State Elementary School for the 2020/2021 academic year. Data collection techniques use teacher performance assessment sheets by the school principal and learning outcomes tests. The results of this research show that the average class score has increased, namely in the pre-cycle it was only 62.27, increasing in the first cycle to 70.90 and increasing again in the second cycle to 76.81. Classical student learning completeness increased, namely from 31.81% in the pre-cycle to 68.18% in the first cycle and increased to 86.36 in the second cycle. Based on this research, it can be concluded that the use of image media can improve the science learning achievement of fifth grade students at Mlese State Elementary School.